Oosterhoff on trusts - Oosterhoff, A. H.; Chambers, Robert; McInnes, Mitchell (Thomson Reuters Canada, 2019)
"New in this edition: Material on aboriginal settlement trusts, sham trusts, gratuitous transfer to trustee of pre-existing trust, resettlement of trust, administrative and cy-près schemes, public appeals (fundraising), rebutting presumptions in context of illegal purposes, personal liability of trustees, exculpatory clauses, and tracing into the payment of a debt. ... updated with new case and statute law, including references to the 2015 Trustees Act of New Brunswick that is based on the Uniform Trustee Act of 2012"–Publisher's website
OCLC: 1107373917